2012
DOI: 10.1007/s10162-012-0349-9
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Paths to Mammalian Cochleae

Abstract: Evolution of the cochlea and high-frequency hearing (920 kHz; ultrasonic to humans) in mammals has been a subject of research for many years. Recent advances in paleontological techniques, especially the use of micro-CT scans, now provide important new insights that are here reviewed. True mammals arose more than 200 million years (Ma) ago. Of these, three lineages survived into recent geological times. These animals uniquely developed three middle ear ossicles, but these ossicles were not initially freely sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 72 publications
(68 reference statements)
1
63
0
Order By: Relevance
“…In the inner ear of vertebrates, the five vestibular end organs devoted to equilibration (utricle, saccule, and three semicircular canals) have remained fairly constant during evolution, whereas the auditory organ has undergone substantial changes that ultimately led to the emergence of the mammalian cochlea containing the electromotile outer hair cells (3,18) (Fig. 1 A and E).…”
Section: Differential Distribution Of Spectrin βV In Amphibian and Mamentioning
confidence: 99%
See 2 more Smart Citations
“…In the inner ear of vertebrates, the five vestibular end organs devoted to equilibration (utricle, saccule, and three semicircular canals) have remained fairly constant during evolution, whereas the auditory organ has undergone substantial changes that ultimately led to the emergence of the mammalian cochlea containing the electromotile outer hair cells (3,18) (Fig. 1 A and E).…”
Section: Differential Distribution Of Spectrin βV In Amphibian and Mamentioning
confidence: 99%
“…The cochlear outer hair cells are unique to mammals, but the existence of somatic electromotility in nonmammalian species has been a matter of debate (2,3,13). Indeed, it has been suggested that a prestin-dependent amplification mechanism also exists in the chicken auditory short hair cells, which could be correlated with the presence of prestin in the plasma membrane of their apical circumference (12).…”
Section: And Ref 30)mentioning
confidence: 99%
See 1 more Smart Citation
“…Evolution of the auditory system has seen a major reinterpretation in the last 20 years or so [Clack, 1997;Carr and Soares, 2002;Manley, 2012;Nothwang, 2016]. It is now agreed that the auditory endorgans (amphibian papilla, basilar papilla or organ of Corti) of the different groups of land vertebrates diverged during a long period of independent evolution.…”
Section: Introductionmentioning
confidence: 99%
“…While there are several characteristics in the postcranial skeleton unique to mammals, such as differentiation of the vertebral series, the shoulder girdle and the limb muscles to permit parasagittal gait and agile locomotion (Bramble & Jenkins, 1989), many distinctive osteological features are focussed in the cranial skeleton. For example, (i) a mediolaterally expanded braincase to accommodate an enlarged brain, (ii) fusion of the palatal processes of the premaxilla and maxilla to form a secondary bony palate separating the oral and nasal cavities, (iii) a unique middle and inner ear morphology capable of high-frequency sound detection, (iv) formation of a single bony housing (petrosal) for the inner ear, (v) an expanded, single bone (dentary) forming the lower jaw, (vi) a novel craniomandibular jaw joint formed by the squamosal and dentary, and (vii) a heterodont dentition differentiated into functional groups with a single (diphyodont) replacement phase between deciduous and permanent teeth (Kielan-Jaworowska, Cifelli & Luo, 2004;Kemp, 2005;Rowe, Macrini & Luo, 2011;Manley, 2012). The sequence of hard-tissue character transformations leading to the development of these characters is remarkably well documented in the fossil record, representing the evolution of a suite of correlated structural innovations rooted in modifications of the feeding and auditory systems (Allin & Hopson, 1992;Sidor & Hopson, 1998;Kemp, 2005;Luo, 2011).…”
Section: Introductionmentioning
confidence: 99%